The concepts `can swim` and `water competition` and their relationship: a conceptual model - Stallman, R. K. (XIIth International Symposium for Biomechanics and Medicine in Swimming, 2014)
Introduction: A concise definition of what swimming really is has yet to be broadly adopted. Such a definition is necessary to advise teachers, instructors and program planners. Appropriate content has protective value in a drowning prevention context. Methods: Four sources of data have been used to construct a definition of `CAN SWIM`: 1) a review of content of 25 well known organisations, 2) in depth interviews with drowning survivors, 3) observation of simulated drowning episodes, 4) theoretical movement analysis. Skill alone is often not enough to prevent drowning. Water competence which includes skill, was defined by polling expert opinion. The relationship between swimming skill and water competence was devised as a conceptual model. Results: The resulting definition of swimming skill focuses on essential protective skill elements in an all-around aquatic skill development. Each of these has a protective value of its own as well as collective value when integrated with each other. Water competence is defined to include skill plus the cognitive and affective competencies which provide additional protection, i.e. attitudes, knowledge, judgement, values and behaviour. The conceptual model of the relationship between swimming skill and water competence places skill as the core of water competence with the affective and cognitive qualities as added protective value. Conclusions: Swimming skill is the core of water competence. To the core is then added all cognitive and affective competencies which increase the protective value on, in and around the water. The minimal teaching package which we should deliver, is a water competence package.